Gualou Xiebai Decoction, a Traditional Chinese Medicine, Prevents Cardiac Reperfusion Injury of Hyperlipidemia Rat via Energy Modulation - Yan, Lu-Lu; Zhang, Wei-Yang; Wei, Xiao-Hong; Yan, Li; Pan, Chun-Shui; Yu, Yang; Fan, Jing-Yu; Liu, Yu-Ying; Zhou, Hua; Han, Jing-Yan; Yao, Xin-Sheng (Frontiers in Physiology, 2018)
Background: Gualou Xiebai Decoction (GLXB) is a classic prescription of Chinese medicine used for the treatment of cardiac problems. The present study was designed to explore the effect and mechanism of GLXB on ischemia/reperfusion (I/R) induced disorders in myocardial structure and function, focusing on the regulation of energy metabolism and the RhoA/ROCK pathway. Methods: After hyperlipidemic rat model was established by oral administration of high fat diet, the rats were treated with GLXB for 6 weeks and subjected to 30 min occlusion of the left anterior descending coronary artery followed by 90 min reperfusion to elicit I/R challenge. Myocardial infarct size was assessed by Evans blue-TTC staining. Myocardial blood flow (MBF) and cardiac function were evaluated. Enzyme-linked immunosorbent assay was performed to examine the content of ATP, ADP, AMP, CK, CK-MB, LDH, cTnT, cTnI and IL-6. Double staining of F-actin and terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling was conducted to assess myocardial apoptosis. Expressions of ATP synthase subunit δ (ATP 5D), and RhoA and ROCK were determined by Western blotting. Results: Administration with GLXB at high dose for 6 weeks protected heart against I/R-induced MBF decrease, myocardial infarction and apoptosis, ameliorated I/R-caused impairment of cardiac function and myocardial structure, restored the decrease in the ratio of ADP/ATP and AMP/ATP, and the expression of ATP 5D with inhibiting the expression of RhoA and ROCK. Conclusions: Treatment with GLXB effectively protects myocardial structure and function from I/R challenge, possibly via regulating energy metabolism involving inactivation of RhoA/ROCK signaling pathway.